A flexible bandwidth resource provisioning system with agent-enhanced SLA negotiation - Chieng, David; Marshall, Alan (IOS Press Amsterdam, 2004)
We present a novel bandwidth resource provisioning system that enables dynamic, flexible and quantitative end-to-end bandwidth reservation and management. The system facilitates agent-enhanced Service Level Agreement (SLA) negotiation and brokering on a per-user, per-application or per-flow basis. In this paper, various session level SLA schemes involving bandwidth allocation, service start time and service duration parameters are introduced and analysed. The results show how these negotiation schemes can be utilised for the benefits of both negotiating parties, such as getting the highest individual SLA optimisation in terms of Quality of Service (QoS) and price.